Empathy and event related potentials before and after EEG based neurofeedback training in autistic adolescents - Julia Fietz; Gabriel Auer; Paul Plener; Luise Poustka; Lilian Konicar (Scientific Reports)
Abstract Autism Spectrum Disorder (ASD) is often characterized by deficits in emotion regulation and empathic abilities, potentially linked to alterations in prefrontal brain regions. This randomized, controlled clinical trial examines the efficacy of slow cortical potential neurofeedback training, specifically targeting these prefrontal areas, in improving emotion regulation and empathy among children and adolescents with ASD. The study involved 41 participants, with 21 undergoing slow cortical potential training and 20 receiving treatment as usual. All participants were allowed to continue usual care in progress, if it was kept stable. Emotional processing was evaluated using an adapted and extended version of the Multifaceted Empathy Test, alongside electroencephalography assessments focusing on event-related potentials, including N170, LPP, and P300 components. The main findings indicate a significant group × time interaction in P300 latency, with shorter latencies in the SCP neurofeedback group and longer latencies in controls, though post hoc tests were not significant. A trend toward reduced P300 amplitude in the experimental group suggests possible modulation of attentional processing. Additionally, changes in a late component of LPP amplitude were linked to reaction time in processing positive emotions, with increases associated with slower responses and decreases with faster responses. These results suggest slow cortical potential neurofeedback training may influence cognitive efficiency and emotional processing in autistic individuals. While promising, further research is needed to confirm these findings and optimize neurofeedback protocols for this population.